2019
DOI: 10.1007/s40868-019-00055-2
|View full text |Cite
|
Sign up to set email alerts
|

Offshore deployments of wave energy converters by Uppsala University, Sweden

Abstract: Ocean can provide an inexhaustible amount of energy. Many marine energy converters have been developed but most of them have not surpassed the experimental phase due to the high costs in installation, operation, and maintenance. Since 2002 Uppsala University has developed and deployed several units of wave energy converters of various designs. The Uppsala University wave energy converter concept consists of a linear generator directly connected to a point absorber buoy that is mounted on a concrete gravity fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The seasonal ice-cover of the Baltic Sea [39,40] is, however, known to influence the wave climate, and Tuomi et al [41] suggested ways to calculate different types of statistics taking the ice-time into account. In practice, experience from both the WESA (Wave Energy for a Sustainable Archipelago) project [42][43][44] and several field tested deployment strategies [45,46] of wave energy equipment have increased the awareness of wave energy as an available potential renewable energy source in the region. Wave energy converters are, however, not very likely to be deployed if the presence of sea-ice is consistent for long periods of time every year.…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal ice-cover of the Baltic Sea [39,40] is, however, known to influence the wave climate, and Tuomi et al [41] suggested ways to calculate different types of statistics taking the ice-time into account. In practice, experience from both the WESA (Wave Energy for a Sustainable Archipelago) project [42][43][44] and several field tested deployment strategies [45,46] of wave energy equipment have increased the awareness of wave energy as an available potential renewable energy source in the region. Wave energy converters are, however, not very likely to be deployed if the presence of sea-ice is consistent for long periods of time every year.…”
Section: Introductionmentioning
confidence: 99%
“…In the first method ( Figure 5a) the buoy is deployed subsequently from its generator. The generator is first lowered to the seabed with a crane while being pressurized [40]. A diver removes the lifting slings and shackles, closes the pressurization valve, and pulls off the pressurization hose.…”
Section: Methods 1-wave Energy Convertors (Wec) and Buoy Deployment Sementioning
confidence: 99%
“…The test sites are located in an area about 10 km off the Swedish west coast, as shown in Figure 2a [34], where the UU Project deploys and tests the WECs. The research site fulfills three important geographical requirements and economic consideration: (a) the seabed is flat enough to accommodate over 10 prototypes of WEC; (b) the nearby harbor offers good accessibility and transmission conditions; and (c) biological and environmental studies are available as the test site is close to biological stations.…”
Section: Wave Energy Project At Uppsala Universitymentioning
confidence: 99%